Clinical and pathological findings in experimental brucellosis in pregnant rats - Rahman Md. Siddiqur,1 Baek Byeong Kirl.2 (The Journal of Infection in Developing Countries, 2008)
Background: To investigate the clinical findings and pathological changes in female Sprague-Dawley rats (SD) after experimental infection at late stage of pregnancy with Brucella abortus biotype 1 Korean isolate. Methodology: Twenty-five rats were used and the rats were classified into two groups, an infected group (n=15) and a control group (n=10). At 18 days of gestation 500 microliters containing 1.0×109colony forming unit (CFU) suspension of B. abortus biotype 1 Korean isolate in physiological saline solution was injected subcutaneously to each of 15 rats, and ten rats were injected with only 500 microliters of physiological saline. The SD rats were examined clinically and the spleen, lymph nodes, uterus and placenta were examined grossly and microscopically. Additionally these organs as well as the blood were cultured bacteriologically.Results: There were no stillbirths, abortions or premature births in any of the SD rats. The gross signs of all the SD rats of the infected group included splenomegaly, metritis, enlargement of lymph nodes and placentitis. Moreover, B. abortus biotype 1 were detected in the organs of infected SD rats as well as in the blood. The microscopic signs of the SD rats of the infected group included infiltrations of macrophages, giant cells and engorged macrophages scattered in necrotic debris in the lymph nodes. In the spleen, there was diffuse congestion of the red pulp, diffuse infiltration of macrophages with increased giant cell numbers and prominent germinal centres. In the uterus, there was moderate, diffuse, but multifocally prominent accumulation of lymphocytes and macrophages in the superficial lamina. In the placenta, there were areas of necrosis in the periplacentomal chorionic epithelium.Conclusions: It is concluded that the Korean pathogenic isolate B. abortus biotype 1 does not induce abortion in SD rats.